The relationship of hardiness and stress - Ho, Khee Hoong; Abdul Kadir, Rusnani (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The primary objective of this study was to assess the level of hardiness and stress of University Putra Malaysia in Malaysia using Cognitive Hardiness Scale (CHS) and Perceived Stress Scale (PSS). 181 undergraduate students selected via cluster random sampling to participate in this study. Questionnaires were used for self-reported measure and data collection. Results showed that majority of the respondents have low stress (58.0%), compared to high stress (42.0%), indicating a relative unhealthy proportion. Moreover, only a small proportion of respondents have high hardiness (23.8%), compared to moderate hardiness (76.2%). The mean score for stress is 41.69 (SD = 5.626), whereas the mean score for cognitive hardiness is 43.30 (SD = 5.399).The results of this study reaffirm the necessity of counseling intervention in tertiary education of Malaysia.